2016
DOI: 10.1186/s13065-016-0176-x
|View full text |Cite
|
Sign up to set email alerts
|

Surface tension examination of various liquid oral, nasal, and ophthalmic dosage forms

Abstract: Surface tension at the surface-to-air interface is a physico-chemical property of liquid pharmaceutical formulations that are often overlooked. To determine if a trend between surface tension and route of administration exists, a suite of oral, nasal, and ophthalmic drug formulations were analyzed. The surface tension at the surface-to-air interface of the oral formulations studied were in or above the range of the surface tension of gastric, duodenum, and jejunum fluids. The range of surface tensions for oral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 15 publications
2
16
0
Order By: Relevance
“…Surface tensions were measured using the ring method [16]. Samples were freshly prepared in a testing flask and allowed to stand for 30 minutes at 22˚C.…”
Section: Critical Micelle Concentrationmentioning
confidence: 99%
“…Surface tensions were measured using the ring method [16]. Samples were freshly prepared in a testing flask and allowed to stand for 30 minutes at 22˚C.…”
Section: Critical Micelle Concentrationmentioning
confidence: 99%
“…The surface tension of natural tears is reported to be 40-46 mN/m [7,8], and the viscosity 1.0-8.3 mPa.s [9,10]. The surface tension of an ophthalmic formulation affects its interaction with the tear film and spreading ability over the ocular surface [25]. In conclusion, the results obtained in this study demonstrated that the liposome-based in situ gelling artificial tear formulation presents suitable properties for topical ophthalmic administration and is well tolerated.…”
Section: Discussionmentioning
confidence: 54%
“…Ophthalmic products were investigated by Han et al, and the range of the surface tension values was between 34.3 mN m −1 and 70.9 mN m −1 . 35 – 37 According to this study, the surface tension of formulations meets the requirements for ophthalmic products.…”
Section: Resultsmentioning
confidence: 91%